Uma abordagem subjetivista da resistência dos executivos à mudança: análise de duas corporações americanas - Garrido, Giovanna (2015)
This study aims to discuss the Resistance to Change as a non rational phenomenon. Aiming to think about the theme by a different focus, the study looks for promoting a reflection about the executive's resistance to change, assigning a view to this individual as a complex subject and considering his subjectivity, unconsciousness and his psychic fragility as central elements for the study of the resistant behavior in the organizations. Based on bibliographic researches of exploratory feature, this study is established in a central idea that, basing in a subjective focus of the resistance phenomenon, is possible to consider the executives' resistant behavior as external reflexes of that is reproduced inside these subjects' psyche. The research that was done showed favorable arguments for this idea. Considering the way that the alienation of these subjects and the consequent occult meaning assigned to organization that they administer influence the way that they interpret the world, is possible to say that a big part of the assumed behavior as regards as the organizational change is resulted from internalized and repressed anxieties, ranging from annihilation fear to way of thinking that symbolizes their core identity. It is noteworthy that, in the search for concretization of this theoretical debate, were analyzed two big happenings of the history of two american organizations, AnheuserBusch and RJR Nabisco, translated in the works of Macintosh (2013) and of Burrough and Helyar (2009), respectively. The analysis and the interpretation of both cases enhance the discussion in favor to a practical content for the issues that were discussed in this study. Reached its aims, the research's results point to the fragility of the predominant approaches as regards as theme and promote openings paths for new researches that could be done via subjective analysis.